ApoA2–256T > C polymorphism interacts with Healthy Eating Index, Dietary Quality Index-International and Dietary Phytochemical Index to affect biochemical markers among type 2 diabetic patients. Issue 9 (14th May 2022) - Esmaeily, Zahra; Sotoudeh, Gity; Rafiee, Masoumeh; Koohdani, Fariba
Abstract: Several investigations revealed the association between ApoA2 concentration and lipid profile, inflammation and oxidative stress markers. Dietary habits also play a major role in the health status of individuals with type 2 diabetes mellitus (T2DM). This study aimed to investigate the interaction of ApoA2–256T > C with dietary indexes on ghrelin and leptin hormones together with biochemical markers among individuals with T2DM. A cross-sectional study was conducted on 726 randomly selected individuals with T2DM. A validated FFQ was used to evaluate Healthy Eating Index, Dietary Quality Index-International (DQI-I) and Dietary Phytochemical Index (DPI). ApoA2–256T > C genotypes were detected by real-time-PCR. Ghrelin, leptin and biochemical markers were also assessed. ANCOVA was used for the interaction between the polymorphism and dietary indexes. A significant interaction was observed between ApoA2–256T > C and DQI-I on high-sensitivity C-reactive protein (hs-CRP) level and superoxide dismutase (SOD) activity. Besides, the interaction of the SNP and DPI significantly affected hs-CRP and 8-isoprostane F2 α (PGF2 α ) levels. CC in the second tertile of DPI had the lowest hs-CRP level, and it was elevated due to adhering to DQI-I ( P interaction = 0·01 and 0·04, respectively). Moreover, T-allele (protective allele) carriers with the highest level of PGF2 α and SOD activity were those in the second tertile of DPI and DQI-I, respectively ( P interaction = 0·03 and 0·007, respectively). SOD activity, hs-CRP and PGF2 α concentration may be modified in T-allele carriers and CC by the adherence to DPI and DQI-I, though additional studies are required to confirm these findings.